Journey of a single cell to a plantlet via in vitro cloning mature trees of conifers - Malabadi, Ravindra B.; Nataraja, K.; Kumar, S. Vijaya; S. Mulgund, Gangadhar (Research in Biotechnology, 2011)
During cloning of mature conifers, isolated somatic cells from apical meristematic tissue under any external stress conidions of cold\heat or chemical are induced to form a somatic embryo. This review paper highlights the difference between embryogenesis patterns in angiosperms and gymnosperms and updates information on the current progress made in the cloning of mature trees of conifers. Insights gained through these systemsÃ‚Â  has already lead to the development of cloning methodologies that could aid in reprogramming apical meristematic cells of recalcitrant mature conifers for clonal forestry.